Additive prognostic value of interleukin-6 at peak phase of dobutamine stress echocardiography in patients with coronary artery disease. A 6-year follow-up study. - Ikonomidis, I; Athanassopoulos, G; Stamatelopoulos, K; Lekakis, J; Revela, I; Venetsanou, K; Marinou, M; Monaco, C; Cokkinos, D; Nihoyannopoulos, P (2008)
BACKGROUND: Interleukin-6 (IL-6) and tissue factor (TF) are elevated after myocardial ischemia during dobutamine stress echo (DSE). We examined the incremental prognostic value of IL-6 or TF measured during DSE over echocardiographic and clinical factors in patients with chronic coronary artery disease (CAD). METHODS: We studied 106 patients with angiographically documented CAD. IL-6 and TF were measured at rest, peak, and during recovery. A wall motion score index was calculated. RESULTS: Fifty-seven (54%) patients had ischemia at DSE. During follow-up (63.7 +/- 20 months), 36 patients (33%) had an adverse event (12 cardiac deaths, 24 acute coronary events). Patients with events had a higher peak IL-6 (P = .02) but similar rest and recovery IL-6 than those without. Patients with peak IL-6 > or =3.14 pg/mL (upper tertile) had a hazard ratio of 2.7 (95% CI 1.44-5.37) (P < .01 for an adverse event). The addition of peak wall motion score index in a multivariable model including risk factors, ejection fraction, revascularization, and multivessel disease increased the model's c statistic from 0.66 to 0.70 (P = .04). The addition of peak IL-6 further increased the model's c statistic to 0.75 (P = .04). Tissue factor was not related with cardiac events. CONCLUSIONS: Interleuikin-6 levels measured during the peak phase of DSE incrementally contribute to risk stratification in patients with chronic CAD.